Perception of Citizen Insecurity - Pillhuamán Caña, Nelly (2010)
This study was carried out in the district of San Juan de Miraflores having as main purpose to obtain reliable information about «perceptions of insecurity and victimization of citizens. The study is a quantitative, descriptive and transversal. The sample design is probabilistic, three-stage, where the final stage unit is the individual whose age is between 16 and 65. The results indicate that in the past six months, 35% of people have been victims of any unlawful act, being theft crime the most common type . Also, 74% of people who have suffered some type of crime, have not filed a complaint before the National Police of Peru (PNP), arguing as the main reason that the PNP is doing nothing about it.